2008
DOI: 10.1029/2007gl033062
|View full text |Cite
|
Sign up to set email alerts
|

A crystalline‐to‐crystalline phase transition in Ca(OH)2 at 8 GPa and room temperature

Abstract: X‐ray diffraction and Raman spectroscopy measurements reveal that Ca(OH)2‐portlandite transforms to a crystalline phase with an ordered OH sublattice between 8 and 14 GPa at room temperature under quasi‐hydrostatic stress conditions in an Ar pressure medium. The amorphization previously reported at 11 GPa under no pressure medium was not observed up to 26 GPa. The width and separation of the fluorescence peaks from the ruby chips embedded in Ca(OH)2 without a medium suggest that deviatoric stress is responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…18 The variation in amorphization pressures among our samples may also be due to subtle differences in the deviatoric stresses between samples. Catalli et al 17 have found the pressure-induced amorphization of Ca͑OH͒ 2 is likely facilitated by nonhydrostatic ͑deviatoric͒ stress and they do not observe this transition in a quasihydrostatic pressure medium ͑argon͒. Although the nonhydrostatic stresses in our system appear to be relatively low ͑Ͻ0.5 GPa at 20 GPa͒, tin iodide may be extremely sensitive to even small deviatoric stresses that change the amorphization pressure by up to several gigapascals.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…18 The variation in amorphization pressures among our samples may also be due to subtle differences in the deviatoric stresses between samples. Catalli et al 17 have found the pressure-induced amorphization of Ca͑OH͒ 2 is likely facilitated by nonhydrostatic ͑deviatoric͒ stress and they do not observe this transition in a quasihydrostatic pressure medium ͑argon͒. Although the nonhydrostatic stresses in our system appear to be relatively low ͑Ͻ0.5 GPa at 20 GPa͒, tin iodide may be extremely sensitive to even small deviatoric stresses that change the amorphization pressure by up to several gigapascals.…”
Section: Discussionmentioning
confidence: 55%
“…The weak intermolecular forces in tin iodide may make it sensitive to even small deviatoric stresses, which can change the amorphization pressure of crystals. 17 At pressures above 15 GPa, all samples appear to behave about the same, apparently due to a more uniform stress environment from sample to sample. Table II.…”
Section: Discussionmentioning
confidence: 94%
“…In order to prevent capturing of H 2 O, the loading was conducted in a dry Ar chamber where the Ar gas pressure was maintained higher than the atmospheric pressure throughout the procedure. In Raman scattering measurements, no detectable amount of H 2 O has been found in an Ar medium [e.g., Catalli et al , ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to prevent capturing of H 2 O, the loading was conducted in a dry Ar chamber where the Ar gas pressure was maintained higher than the atmospheric pressure throughout the procedure. In Raman scattering measurements, no detectable amount of H 2 O has been found in an Ar medium [e.g., Catalli et al, 2008]. Synchrotron X-ray diffraction (XRD) patterns were measured in situ at high P-T in double-sided LHDAC at beamline 13-IDD of the GeoSoilEnviroConsortium for Advanced Radiation Sources (GSECARS) sector and beamline 16-IDB of the High Pressure Collaborative Access Team (HPCAT) sector [Meng et al, 2006] at the Advanced Photon Source.…”
Section: Methodsmentioning
confidence: 99%
“…At each corner of an octahedron, each O atom binds one H atom and the latter interacts with three neighboring hydroxyl groups of the adjacent layer. Early studies on bulk AEMHs revealed that the application of temperature and pressure may result in dramatical changes in their crystal structure and their electronic properties [11][12][13][14][15][16][17][18]. Moreover, early theoretical studies showed the reliability of the use of first principles calculations with a plane-wave basis set in combination with the generalized gradient approximation exchange-correlation functional for the investigation of structural and electronic properties of these materials [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%